Women and Shakespeare in the Eighteenth Century - Ritchie, Fiona (New York : Cambridge University Press, 2014)
"Fiona Ritchie analyses the significant role played by women in the construction of Shakespeare's reputation which took place in the eighteenth century. The period's perception of Shakespeare as unlearned allowed many women to identify with him and in doing so they seized an opportunity to enter public life by writing about and performing his works"--
Machine generated contents note: Introduction: women and Shakespeare in the Restoration; 1. Actresses in the age of Garrick; 2. Female critics in the age of Johnson; 3. Theatrical women respond to Shakespeare; 4. Jordan and Siddons: beyond Thalia and Melpomene; 5. Women playgoers: historical repertory and sentimental response; Conclusion: part of an Englishwoman's constitution; Bibliography.
Includes bibliographical references (p. 227-243) and index.
Young Readers.
Keywords: Shakespeare, William, -- 1564-1616 -- Influence; Women and literature -- History -- 18th century; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh